The Amalfi curse : [large type] a novel - Penner, Sarah (Thorndike Press large print high octane., 2025)
"Haven Ambrose, a nautical archaeologist, has come to Positano to investigate the mysterious shipwrecks along the Amalfi Coast. But she is secretly on a quest to locate a trove of priceless gemstones her late father spotted on his final dive. Upon Haven's arrival, strange maelstroms and misfortunes start plaguing the town. Is it nature or something more sinister? As Haven searches for her father's sunken treasure, she begins to unearth a centuries-old tale of ancient sorcery and stregheria, a magical ability to harness the ocean. Could this magic be behind Positano's latest calamities? Haven must unravel the Amalfi Curse before the region is destroyed forever"--